Studi Perbandingan Daya dan Konsumsi Energi Dispenser: Kontrol PID vs. Kontrol Termostat - Nugroho, Ferdinand Kristantyo; Supardi, Tri Wahyu (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
The production of electrical energy still relies on fossil fuels which produce greenhouse gas emissions and cause global warming. This issue requires a more efficient and effective use of electrical energy. On the other hand, electricity remains an essential daily need, such as for powering hot water dispensers. However, traditional on-off dispensers operate at maximum power, leading to potential household disruptions. It would be more beneficial if dispensers did not use maximum power while maintaining their temperature during standby. This research aims to propose a solution to reduce power usage and suppress electricity consumption in dispensers.This study implements PID control in a hot water dispenser to gather information on its power and energy consumption. Using the Ziegler-Nichols method, tuning parameters were determined as follows: Kp=15.0261, Ki=0.1633, and Kd=345.6. Data acquisition for temperature, power, and energy was conducted on the on-off thermostatic dispensers set at 80°C and 93°C, as well as on PID-controlled dispensers with setpoints at 80°C and 93°C. The results indicate that the PID-controlled dispenser uses only 30% of the maximum power, although the total energy consumption increases by 17Wh to 57Wh due to the need to maintain the temperature close to the setpoint